Myanmar : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Myanmar. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that Myanmar's economy grew broadly as expected in FY2015/16, at a healthy pace of 7.3 percent, despite massive floods during July-September 2015. Activity softened during the first half of FY2016/17, but is expected to recover in the second half on account of the resumption of construction in Yangon after a temporary halt for regulatory compliance purposes. The growth of agricultural production was softer than expected. The external environment has been weak owing to slowing demand from major trading partners and significant natural gas and other commodity price declines in 2015 and 2016. Macroeconomic imbalances persist, with continuing inflation pressure, an increased fiscal deficit, and a widening external current account deficit.